2009
DOI: 10.1121/1.3158599
|View full text |Cite
|
Sign up to set email alerts
|

A note on noise propagation in street canyons

Abstract: The current study examines the propagation of sound in street canyons with geometrically reflecting surfaces. An image source method is a popular numerical model to estimate the propagation of sound energy in a street canyon. This numerical model calculates the total sound energy received at a field point by summing the contributions from individual image sources incoherently. The discrete image source model is generalized by replacing rows of point sources with their respective line sources. An integral formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, the measurement configurations in the five streets were the same in this study, as shown in Figure 4f. The source was placed at the center of the street and 10 receivers were placed along the central axis at distances of 5 to 50 m from the source at intervals of 5 m. Because the most common source and receivers in the measured streets are the pedestrians, the height of the source and receivers were set at 1.25 m, as commonly used in previous measurements [38] and parameter studies [19]. During the measurements, the pistol, omnidirectional source, and sound meter were fixed to supports.…”
Section: Measurement System and Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the measurement configurations in the five streets were the same in this study, as shown in Figure 4f. The source was placed at the center of the street and 10 receivers were placed along the central axis at distances of 5 to 50 m from the source at intervals of 5 m. Because the most common source and receivers in the measured streets are the pedestrians, the height of the source and receivers were set at 1.25 m, as commonly used in previous measurements [38] and parameter studies [19]. During the measurements, the pistol, omnidirectional source, and sound meter were fixed to supports.…”
Section: Measurement System and Configurationmentioning
confidence: 99%
“…As shown in Figure 4, all the building façades were made of glass and concrete, which can be considered as reflective materials in the frequency range of 500-1000 Hz. Measurements and estimations have been carried out for similar materials [38]. The absorption coefficient of the building façades varied from 0.03 to 0.09 in the range of 400-4000 Hz.…”
Section: Estimation Of Acoustic Parameters Of Building Façadesmentioning
confidence: 99%
“…In modeling the sound propagation within a street canyon, the effects of the open ceiling must be taken into account. In the high frequency approximation the height of the canyon is either assumed as infinite 9,10,12 or, equivalently, the opening at the top is represented by a perfectly absorptive ceiling 11 . At lower frequencies, the effect of the finite height of the streets and the radiation of sound above is considered in 6,13,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the urban acoustics literature has been predominantly concerned with noise levels in city street canyons, which has led to the creation of many models that adequately describe portions of the urban noise field and can be used to explore methods of noise abatement (1)(2)(3)(4). Many of the current models used only treat a two-dimensional slice of the urban environment (5, 6) with good results.…”
Section: Introductionmentioning
confidence: 99%